Factors associated with the prevalence of circulating antigens to porcine cysticercosis in three villages of burkina faso. - Rasmané Ganaba; Nicolas Praet; Hélène Carabin; Athanase Millogo; Zékiba Tarnagda; Pierre Dorny; Sennen Hounton; Adama Sow; Pascal Nitiéma; Linda D Cowan (PLoS Neglected Tropical Diseases)
Background little is known about porcine cysticercosis in Burkina Faso. We conducted a pilot study to estimate the prevalence of antigens of Taenia solium cysticercosis and to identify associated factors in pigs of three villages in Burkina Faso, selected to represent different pig management practices: one village where pigs are allowed to roam freely (Batondo), one village where pigs are penned part of the time (Pabré) and one village with limited pig farming (Nyonyogo). Methods/principal findings a clustered random sampling design was used. Data on socio-demographic characteristics (source of drinking water, presence of latrines in the household, type and number of breeding animals) and pig management practices were collected using a standardized questionnaire. Blood samples were collected from one pig per household to determine the presence of antigens of the larval stages of T. solium by the B158/B60 Ag-ELISA. The associations between seropositivity and socio-demographic and pig management practices were estimated using logistic regression. Proportions of 32.5% (95% CI 25.4-40.3), 39.6% (31.9-47.8), and 0% of pigs, were found positive for the presence of circulating antigens of T. solium in Batondo, Pabré, and Nyonyogo, respectively. The results of the logistic regression analyses suggested that people acquire knowledge on porcine cysticercosis following the contamination of their animals. The presence of antigens in the pigs' sera was not associated with the absence of latrines in the household, the source of drinking water or the status of infection in humans but was associated with pig rearing practices during the rainy season. Conclusions/significance the results suggest that education of pig farmers is urgently needed to reduce the prevalence of this infection.